2014
DOI: 10.1039/c3em00731f
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and enzymatic responses to petroleum contamination

Abstract: The changes in microbial ecology interpreted from taxonomic and functional genes and biological functions represented by urease and dehydrogenase activities were monitored in soil contaminated with different petroleum hydrocarbons including crude oil, diesel, n-hexadecane and poly-aromatic hydrocarbons (PAHs). It was shown that the presence of n-hexadecane stimulated the activity of indigenous microorganisms, especially alkane degrading bacteria, and led to over 20% degradation of n-hexadecane within one month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 58 publications
(60 reference statements)
2
25
1
Order By: Relevance
“…Soil I, which was the least contaminated one, had the lowest activities of urease and alkaline phosphatase. Contrary to some other studies (Gianfreda et al 2005, Turgay et al 2010, Wu et al 2014) no correlation was observed between urease activity and the level of PAHs. Thus, the variations in enzyme activities between soil samples showed that in tested soils pollution inputs have specifi c site effects, which may be a result of lower sensitivity of local microbial communities to PAHs and heavy metals.…”
Section: Enzyme Activitycontrasting
confidence: 51%
See 1 more Smart Citation
“…Soil I, which was the least contaminated one, had the lowest activities of urease and alkaline phosphatase. Contrary to some other studies (Gianfreda et al 2005, Turgay et al 2010, Wu et al 2014) no correlation was observed between urease activity and the level of PAHs. Thus, the variations in enzyme activities between soil samples showed that in tested soils pollution inputs have specifi c site effects, which may be a result of lower sensitivity of local microbial communities to PAHs and heavy metals.…”
Section: Enzyme Activitycontrasting
confidence: 51%
“…Both the most contaminated (II) and the least contaminated (I) soils exhibited a noticeable separation from the two other soils in the fi rst principal component (PC1), which explained 78.5% of the variation in the data. The reason for these fi ndings may be the selection and adaptation of microorganisms to the pollutants, which cause a lack of species or strains capable to degrade a variety of carbon sources (Wu et al 2014). The second PCA analysis was carried out for physicochemical data, Σ16PAHs concentrations and enzymatic activities (Fig 2B).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Their RS index nearly approached the value of one, and ranged from 0.91-0.95. The varied response of microorganisms to the tested contamination was associated with their succession (Vázquez et al 2013) resulting from the death of sensitive microorganisms, and the multiplication of the resistant ones (Wu et al 2014). Changes to the multiplication of microorganisms in the soil contaminated with diesel oil may result from the fact that hydrocarbons, as the chemical compounds with a various degree of bioresistance, are degraded at different rates, and they have an effect on the soil microbiota in consequence (Semrany et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Some other intense oil spill examples are the tanker collision in the Mumbai coast and the oil spill in Montora (Sakthipriya et al, 2015) Microbial communities are known to control most major processes that occur in the marine environment (Karl, 2007). One important function and process is biodegradation of contaminants and nutrient recycling that helps to ensure an effective and efficient ecosystem (Wu et al, 2014). Hydrocarbon degradation by microorganisms has received much consideration because of its unhazardous, inflammability, extensive and environmentally friendly state when likened to other orthodox methods (Sakthipriya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%